3rd ICTs and Society Meeting; Paper Session - Theorizing the Internet; Paper 1: Toward Trust as Result. A Transdisciplinary Research Agenda for the ‘Future Internet’ - Stefano De Paoli; G. R. Gangadharan; Aphra Kerr; Vincenzo D’Andrea; Martin Serrano; Dmitri Botvich; Jimmy McGibney (tripleC: Communication, Capitalism & Critique)
Trust has emerged as one of the key challenges for the Future Internet and as a key theme of European research. We are convinced that a transdisciplinary research agenda - that we define to as Trust as Result - shared by Sociology and Computer Science, is of paramount importance for devising sustainable Trust solutions for the (Future) Internet stakeholders. The scope of this paper is to present some elements we consider important for building such an agenda.